ENHANCING SENGGIGI AS A LOMBOK TOURISM DESTINATION: A DEVELOPMENT STRATEGY - Sulfardin; Fatmawati; Suheldi, Rizki; Juniati; Zitri, Ilham; Ali, Muhammad; Jaelani, Muhammad Aprian (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
Tourism holds immense potential to generate significant benefits for the local economy and communities in Senggigi, Indonesia. However, realizing these benefits requires the implementation of effective strategies for developing tourism destinations. This study explores various strategies for fostering tourism in Senggigi, encompassing infrastructure and facility enhancement, promotional and marketing endeavors, bolstering the local community's capacity for tourism, and garnering support from both governmental and private entities. Moreover, it underscores the paramount importance of engaging the local community in the development process, emphasizing consultation, empowerment, and the mitigation of social and economic impacts. Furthermore, the study advocates for sustainable tourism practices that prioritize environmental protection and the preservation of cultural heritage, alongside robust mechanisms for regulating and enforcing policies to prevent their violation. By adopting and implementing these strategies, Senggigi can ensure that its tourism industry optimally benefits the local community while upholding sustainability and competitiveness in the broader tourism market.